Factores predisponentes y morbimortalidad materno-perinatal asociados a la cesárea en el hospital regional de Loreto Punchana – Iquitos periodo : Diciembre 1994 - Noviembre 1995 - Romero Panduro, Jacki (1995)
The present study, type applied with prospective data collection, was developed in the Regional Hospital of Loreto, period 1 December 1994 through 30 November 1995; pair known predisposing factors and maternal and perinatal morbidity and mortality associated with caesarean section and compare the results with those of other studies and thus have knowledge according to our reality. Of a total of 2044 deliveries attended during the period established 186 cases of cesarean were found; which represents 9, 60% of the monthly average and 9.58% annual average total cesarean, 71.43% were performed emergency and 28.57%, on a scheduled basis. Almost 20% of patients in both groups were teenagers cesarean. The 72.15% for emergency caesarean sections and 50% in elective caesarean sections were single mothers or cohabiting. Regarding the level of education is not illiterate patients was found. More than two thirds of cesarean come from urban areas and are of low socio-economic status. Regarding the history of reproductive and nulliparous patients more frequently observed in emergency caesarean sections, whereas in elective caesarean sections, the frequency was higher in patients with 1-2 children. Similarly, a high percentage of patients not controlled or inadequate prenatal care in both who had emergency caesarean sections and those with scheduled cesareans observed. The most practiced type of uterine incision was the segmental (93.43% in emergency caesarean sections and 100% in the set) and was mostly done by gynaeco-obstetricians medical headlines. The type of anesthetic that was applied antibiotic prophylaxis spinal and were prescribed for 90.82% of all patients. The main predisposing factors as a cause of cesarean were hypertensive disease of pregnancy, previous caesarean section, fetal distress, third-trimester bleeding, pelvic presentation primigesta and failed induction. Some of these factors are unique to emergency caesarean sections or programmed, while others are in both. The average hospital stay was 4.88 days in emergency caesarean sections and 4.91 days scheduled cesareans. A large percentage of patients who had high voluntary (23.43% in emergency caesarean sections and 34.29% for scheduled cesareans) also observed. Almost half of cesarean (47.45%) had postpartum morbidity, the most frequent arterial hypertension, anemia, endometritis, fever of unknown origin and wound infection _ Perinatal morbidity was 60 .33% of all newborns and was mainly caused by the NPI, hypoxia and prematurity, meconium aspiration syndrome and pathologic jaundice. Both maternal morbidity, such as perinatal was higher in emergency caesarean sections at scheduled, representing a highly significant difference. Maternal mortality was around 50 per 10,000 births by cesarean section and only occurred in emergency caesarean sections. The perinatal mortality rate was 7.62% per 1,000 births; loa 5.37 per thousand which corresponds to the stillbirth and 2.45 per thousand to early neonatal mortality. Mortality was higher in emergency cesarean sections.